Effect of Radiation, Organic Solvents and Vibration Occupational Exposure on the Thyroid Disease: Results from Project ELEFANT - Bibo Yuan; Citlalli Osorio-Yáñez; Junkai Fang; Lei Zhao; Ander Wilson; Marco Sanchez-Guerra; Hongbin Liu; Peng-Hui Li; Liqiong Guo (Aerosol and Air Quality Research)
Abstract Although occupational exposure to radiation and organic solvents has been proven to increase the chance of developing thyroid disease, one of the leading endocrine disorders, much less is known about the potential risk factor of vibration exposure. Thus, this study aimed to examine the relationships between occupational exposure to radiation, organic solvents and vibration, and thyroid disease risk and thyroid-stimulating hormone (TSH) levels by utilizing data sets from Project ELEFANT, which comprises 124,286 participants from Tianjin, China. We reviewed the medical records, including the thyroid disease history, of young adult participants and measured the TSH levels in the females via automated immunometric assay. Logistic models adjusted for confounders revealed significant associations between exposure to radiation (odds ratio [OR]: 1.73; 95% confidence interval [CI]: 1.1–2.7), organic solvents (OR: 2.0; 95% CI: 1.3–2.9) and vibration (OR: 4.4; 95% CI: 2.0–8.75), and an increased risk of thyroid disease. Additionally, the TSH concentrations in the female participants (median: 1.95; 95% CI: 2.45–2.77) displayed a correlation exclusively with vibration exposure (β: 2.80; 95% CI: 1.07–4.54). Our results show, for the first time, that vibration exposure is associated with an increased risk of thyroid disease and elevated TSH levels. If these findings are confirmed in other cohorts, thyroid examinations should be conducted for individuals exposed to vibration in the workplace.